(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2024)
The following text proposes several reflexions about the particularities that creating a dramaturgy for a Lambe Lambe Theatre play involves such as the image as the main idea of the dramaturgy, build a point of view, find the synthesis, compose the internal and external choreographies, and the soundscape as an amplifying of the universe of the play. These reflections come from the several experimentations with objects, sounds, images and materials that the author has used as creative ways to design and make her own Lambe Lambe Theatre plays.